TRPC6 knockdown-mediated ERK1/2 inactivation alleviates podocyte injury in minimal change disease via upregulating Lon peptidase 1 - Jianwei Ma; Liling Ren; Qin Su; Xiuyi Lv; Min Sun; Yunbo Wei; Lili Dai; Xueyan Bian (Renal Failure)
Minimal change disease (MCD) is a universal primary glomerular disease contributing to nephrotic syndrome. Lon peptidase 1 (LONP1) has been suggested to protect podocytes from damage during the progression of MCD. Accordingly, our research further explored the specific mechanisms of LONP1. Initially, the expressions of TRPC6, p-ERK1/2, and LONP1 in the kidney tissues of MCD patients were detected by immunohistochemistry and Western blot. Human podocytes AB8/13 were serially subjected to transfection with shTRPC6/shNC, and 48-h treatment with 30 µg/ml puromycin aminonucleoside (PAN). The viability, apoptosis, and migration of AB8/13 cells were assessed by cell counting kit-8, flow cytometry, and transwell assays. The mRNA and protein expressions of LONP1 were downregulated while those of TRPC6 were upregulated in the kidney tissues of MCD patients. PAN induced podocyte injury and migration and inhibited LONP1 expression, whereas TRPC6 silencing did oppositely. The phosphorylation level of ERK1/2 was reduced in MCD samples, which was negatively associated with TRPC6 expression and positively associated with LONP1 expression. Furthermore, ERK phosphorylation agonist offset the effects of TRPC6 silencing on mitigating podocyte injury and migration as well as upregulating LONP1 expression. Collectively, TRPC6 knockdown-induced ERK1/2 inactivation can ameliorate podocyte injury in MCD by increasing the expression of LONP1.